Выбор микропривода механизма зажима и подачи проволоки в установках термозвуковой микросварки - Lanin, V. L.; Petukhov, I. B.; Shevtsov, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The article describes research of three types of wire clamp microdrive for thermosonic microwelding equipment, covering an expanded range microconductors from 12,5 up to 75 mm. The most preferable, in the light of their high-speed and easy-programming qualities, proved to be the mechanisms of conductor clamp with piezoelement drives and the loading system based on "voice-coil" type electromagnet.